(untitled) (Boston, 2008)
The new edition of Essentials of Business Statistics delivers clear and understandable explanations of core business statistics concepts, making it ideal for a one term course in business statistics. Containing continuing case studies that emphasize the theme of business improvement, the text offers real applications of statistics that are relevant to today's business students. The authors motivate students by showing persuasively how the use of statistical techniques in support of business decision-making helps to improve business processes. A variety of computer centered examples and exercises, and a robust, technology-based ancillary package are designed to help students master this subject.
Keywords: Commercial statistics,Thống kê thương mại